2014
DOI: 10.1002/adma.201401123
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Homogeneous Ductility of Micrometer‐Sized Metallic Glass

Abstract: Homogeneous ductile flow of metallic glasses is observed at the micrometer scale. It is shown that this unusual deformation mode of an otherwise brittle material depends on both specimen size and applied loading rate. The results are explained by intrinsic length-scale effects of nanometer-sized defects, and provide a rationale for the long term debated brittle-to-ductile transition of amorphous metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 50 publications
6
41
1
Order By: Relevance
“…2a. Moreover, this also agrees well with the lower m observed under macro-compression [32] than micro-pillar compression [33]. When the peak-load increases to larger than a critical value, the overall unstable plastic flow (the advent of a mature shear band) will occur immediately once the indenter presses into the metallic glass [20].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 76%
“…2a. Moreover, this also agrees well with the lower m observed under macro-compression [32] than micro-pillar compression [33]. When the peak-load increases to larger than a critical value, the overall unstable plastic flow (the advent of a mature shear band) will occur immediately once the indenter presses into the metallic glass [20].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 76%
“…The shear offsets seen on the pillars' surfaces in the accompanying micrographs suggest that the pop-ins in these stress-strain curves correspond to shear banding events. That these pillars deform by shear localization is consistent with past reports on the microcompression testing of metallic glass pillars with diameters [1 lm [41][42][43][44]. In most tests, only a single pop-in was observed, followed by pillar failure but occasionally tests captured multiple pop-in events, separated by regions of continued elastic deformation.…”
Section: Resultssupporting
confidence: 78%
“…In light of other studies on taper-free metallic glass pillars with similar dimensions, this yield strength would likely match that of bulk specimens if such specimens could be prepared [25,26,44]. The other phenomena seen in these microcompression tests are consistent with prior studies on the microcompression testing of metallic glasses, confirming that microcompression testing of powder particles can be used to extract a powder's intrinsic deformation behavior.…”
Section: Resultssupporting
confidence: 75%
“…Very recently, Volkert et al [24] revealed that SRS kept constant among the samples with different sizes, indicating the same underlying mechanism in both localized and homogeneous deformation. This implies that the STZs play an important role on the apparent size effect of plastic deformation in metallic glasses.…”
Section: Introductionmentioning
confidence: 96%